Marketing Strategies in Financial Services of Emerging Economies: A Case Study on the Indian Banking Industry - Prakash Khatri, Pavan (2009)
Since 1991, after liberalization came about, India through social reforms had opened its market doors to foreign trade and investments by relaxing their government norms and regulations (www.indhistory.com, Manghirmalani,2008) . This brought about the start of the financial service sector which started dominating the growth of the economy and became the largest contributor to the country’s GDP in the time to follow. (www.mapsofindia.com).Today, the Indian financial services sector forms the second largest component in the entire services sector in a government budget. Thus, explaining the latent dormancy in this sector.